Zebrafish as an Emerging Model for Osteoporosis: A Primary Testing Platform for Screening New Osteo-Active Compounds - Bergen, Dylan J. M.; Kague, Erika; Hammond, Chrissy L. (Frontiers in Endocrinology, 2019)
Osteoporosis is metabolic bone disease caused by an altered balance between bone anabolism and catabolism. This dysregulated balance is responsible for fragile bones that fracture easily after minor falls. With an ageing population, the incidence is rising and as yet pharmaceutical options to restore this imbalance is limited, especially stimulating osteoblast bone-building activity. Excitingly, output from large genetic studies on people with high bone mass (HBM) cases and genome wide association studies (GWAS) on the population, yielded new insights into pathways containing osteo-anabolic players that have potential for drug target development. However, a bottleneck in development of new treatments targeting these putative osteo-anabolic genes is the lack of animal models for rapid and affordable testing to generate functional data and that simultaneously can be used as a compound testing platform. Zebrafish, a small teleost fish, are increasingly used in functional genomics and drug screening assays which resulted in new treatments in the clinic for other diseases. In this review we outline the zebrafish as a powerful model for osteoporosis research to validate potential therapeutic candidates, describe the tools and assays that can be used to study bone homeostasis, and affordable (semi-)high-throughput compound testing.